Non-utilisation of postpartum services in northwestern Nigeria: analyses of trend and social determinants from 2003 to 2018 - Dyah Anantalia Widyastari; Abubakar Abbani Yakubu; Yothin Sawangdee; Pojjana Hunchangsith (BMJ Open)
Objective To assess the prevalence of non-utilisation of postpartum services in northwestern Nigeria from 2003 to 2018 and to identify and estimate the influence of social determinants, a crucial step in improving maternal and child health in the region.Design The 2003, 2008, 2013 and 2018 Nigeria Demographic and Health Survey rounds were used. Descriptive, trend and multivariable logistic regression analyses were used to show the trend and assess the influence of social determinants. The sample consisted of 17 294 women aged 15–49 who responded to questions on postpartum attendance during the period.Setting Northwestern geographical subregion of Nigeria.Outcome The non-use of postpartum services.Results The non-utilisation of postpartum services has increased from 77% in 2003 to 87% in 2018, with an overall prevalence of 88% of all women not using the services. The odds of not using postpartum services were higher for women with no education (adjusted OR (AOR): 1.27; CI: 1.03 to 1.58), those with no knowledge of contraceptives (AOR: 1.72; CI: 1.35 to 2.19), those who never used contraceptives (AOR: 1.71; CI: 1.39 to 2.09), those with parity of four or more births (AOR: 1.58; CI: 1.34 to 1.86), those in polygynous marriage (AOR: 1.16; CI: 1.03 to 1.30) and those from the poorest (AOR: 2.34; CI: 1.67 to 3.28) and poorer (AOR: 2.05; CI: 1.50 to 2.78) households. The odds were lower for women who wanted to delay pregnancy (AOR: 0.74; CI: 0.55 to 0.99) and those with full (AOR: 0.56; CI: 0.42 to 0.75) or joint (AOR: 0.67; CI: 0.53 to 0.83) autonomy in healthcare decisions.Conclusion The findings are crucial for understanding and addressing the non-utilisation of postpartum services in northwestern Nigeria. Policymakers should aim to address the impacts of the identified social determinants to promote the use of postpartum services, prevent maternal deaths and meet the SDG-3.1 target.